New method of internal fixation in laparoscopic Tenckhoff catheter placement. Issue 6 (22nd April 2022) - Peng, Jianwei; Lin, Hanfei; Cai, Chudan; Cai, Cong; Yang, Lihua; Peng, Yanqiang; Wu, Kefei
Abstract: Background: Despite obvious advantages of peritoneal dialysis (PD), mechanical complications are responsible for the failure of PD at early stage. Suture fixation in laparoscopic PD catheter method could reduce mechanical complications. In our study, a simple method to fix PD catheter was developed. Methods: Tenckhoff catheter placement was performed in 49 consecutive patients. In the technique, only two trocars were used. With the help of syringe needle and forceps, a loop of silk was prepared at the abdominal wall. The PD catheter was thread through the loop. The silk ligature was tied subcutaneously keeping the catheter suspended from the abdominal wall. Primary outcomes were catheter‐related complications. Secondary outcomes were 6‐month catheter survival rates and death within 30 days. Data were analyzed retrospectively. Results: The average operation time was 49.7 ± 15.8 min. Minimum follow‐up time was 6 months. No catheter displacement or hernia was detected. One patient had omental wrapping after silk suture rupture, 2 patients had outflow obstruction, and 3 patients had leakage. No one died within 30 days postoperatively. Catheter survival was 95.8% at 6 months. Conclusions: The method we described greatly reduced the risk of catheter displacement and omental wrap. Also, the required instrument and laparoscopic skill were simple.